Wireless physical layer network coding in potential presence of malicious relays – incomplete information game approach. Issue 16 (1st August 2015) - Hynek, T.; Sykora, J.
Abstract : A wireless physical layer network coding (WPLNC) technique in a decentralised and distributed relay network where a maliciously behaving relay may be present is studied. Most research has optimistically assumed altruistic cooperation of relays. The malicious node can lead to a significant disorder among the other relays by selecting its own WPLNC mapping. This scenario is described as a static (single‐shot) incomplete information game where a node type – either friendly or malicious – of the relay is its private information. The focus is on the existence of particular equilibria given the probability of the presence of a malicious node.